(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1991)
SEM and peel observations were carried out on two taxa of the genus Anisactinella Bittner, 1890, namely Anisactinella quadriplecta (Münster, 1847) and Anisactinella maurensis Taddei Ruggiero, 1968. The presence of a peculiar morphologic structure, herein named external apophysis of the cardinal process, has been observed for the first time. The function of this structure may be the hindrance of the opening of the shell. In fact, the morphology of both the valves and the brachidium, as well as their relationships are efficient only if the valves open slightly. This may account for the presence of the external structure. Anisactinella quadriplecta recovered from the San Cassiano Formation, Cortina d’Ampezzo area (Belluno) is revised. Its high variability has been put to evidence on the basis of a crytical analysis.